Homophily and Transmission of Behavioral Traits in Social Networks - Palaash Bhargava; Daniel L. Chen; Matthias Sutter; Camille Terrier (Center for Economic Studies and ifo Institute (CESifo), 2023)
Social networks are a key factor of success in life, but they are also strongly segmented on gender, ethnicity, and other demographic characteristics (Jackson, 2010). We present novel evidence on an understudied source of homophily: behavioral traits. Behavioral traits are important determinants of life outcomes. While recent work has focused on how these traits are influenced by the family environment, or how they can be affected by childhood interventions, little is known about how these traits are related to social networks. Based on unique data collected using incentivized experiments on more than 2,500 French high-school students, we find high levels of homophily across all ten behavioral traits that we study. Notably, the extent of homophily depends on similarities in demographic characteristics, in particular with respect to gender. Furthermore, the larger the number of behavioral traits that students share, the higher the overall homophily. Using network econometrics, we show that the observed homophily is not only an outcome of endogenous network formation, but is also a result of friends influencing each others' behavioral traits. Importantly, the transmission of traits is larger when students share demographic characteristics, such as gender, have longer periods of friendship, or are friends with more popular individuals.
Keywords: D85; C91; D01; D90; 330; homophily; social networks; behavioural traits; peer effects; experiments